The impact of airborne pollution on atopic dermatitis: a literature review. (15th January 2020) - Hendricks, A.J.; Eichenfield, L.F.; Shi, V.Y.
Summary: The increasing prevalence of atopic dermatitis (AD) parallels a global rise in industrialization and urban living over recent decades. This shift in lifestyle is accompanied by greater cutaneous exposure to environmental pollutants during the course of daily activities. The objectives of this review are to highlight the effects of airborne pollution on epidermal barrier function, examine evidence on the relationship between pollutants and AD, synthesize a proposed mechanism for pollution‐induced exacerbation of AD, and identify potential methods for the reduction and prevention of pollutant‐induced skin damage. The literature review was done by searching the PubMed, Embase and Google Scholar databases. Inclusion criteria were in vitro and animal studies, clinical trials and case series. Non‐English‐language publications, review articles and case reports were excluded. Pollutants induce cutaneous oxidative stress and have been shown to damage skin barrier integrity by altering transepidermal water loss, inflammatory signalling, stratum corneum pH and the skin microbiome. AD represents a state of inherent barrier dysfunction, and both long‐ and short‐term pollutant exposure have been linked to exacerbation of AD symptoms and increased AD rates in population studies. Airborne pollutants have a detrimental effect on skin barrier integrity and AD symptoms, and appear to pose a multifaceted threat in AD through several parallel mechanisms, including oxidative damage, barrier dysfunction, immune stimulation and propagation of the itch–scratch cycle. Future research is needed to elucidate specific mechanisms of pollution‐induced epidermal barrier dysfunction and to identify efficacious methods of skin barrier repair and protection against pollutant‐driven damage. Abstract : Plain language summary available online